Stateful library service system design and implementation in Saudi Arabia - Arif Bramantoro (Institute of Advanced Engineering and Science, 2020)
Service system has become one of the most challenging research issues in industry. Most of organizations in Saudi Arabia build their services with state-less technique to avoid many issues although there are some acknowledged advantages of using state-full technique. These issues are mainly related to the low number of visitors, low number of services, storage capacity and organization size. The purpose of this research is to create services that have capability in reading all required data from library management system, improving the service by applying state-full technique. Technology acceptance model is used to measure the acceptance of state-full service system through organizations and customers which gave some prediction to library high management to support them in decision making.